The spaniards conflict at the process of emancipation: Rio de La Plata and Mexico cases at the beginning of the 19th century - León Matamoros, María Graciela (Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2010)
The wars of independence in Latin America and the consequent process of building the nation accounted for the Spaniards unsteadiness, reflected, in various degrees of intensity, in emerging countries. The intent of this paper is to present the measures that the governments of two different territories such as Mexico and Río de la Plata, adopted against the Spaniards for legitimacy. The position of both governments reveal the relationships and affronts which every country kept to their former conquerors, and the levels of dependence on the Iberian that made inoperable, in many cases, the intention of decrease their privileges. Therefore the aim is to show the history, the parallels and differences that these countries had in their provisions against the Spaniards.